RESPONSE OF Gammarus pulex TO LOW CONCENTRATIONS OF ERYTHROMYCIN - OGUNBANWO, O. M (Nigerian Journal of Fisheries, 2018)
Pharmaceuticals are manufactured for the benefit of mankind and used for specific biological functions in veterinary and human medicine. However, these substances after use enter the aquatic environment through different sources either as parent compounds, metabolites or a combination of both. There are significant research gaps for thousands of existing pharmaceuticals with regards to their potential ecological consequences on non-target species. Pharmaceutical pollution is an emerging area of research in Africa and no work had been done in Nigeria on effects of pharmaceuticals in river systems. In this study, the biological effects of one of the most frequently detected pharmaceuticals in the aquatic environment, erythromycin was investigated at environmentally relevant concentrations reported for UK Rivers. Seventy-five (75) Gammarus pulex were employed in the laboratory experiments. Exposure resulted in statistically significant decreases in feeding, growth and an increase in mortality. The feeding rate in the control groups were higher than those in the treatment groups and G. pulex in the control groups gain weight. Mortality among the treatment groups were consistent compared to the controls. Although pharmaceuticals are indispensable to human health, but their usage and discharge into the aquatic environment may lead to ecological problems and antibiotic resistance.